Об одном классе бесконечномерных линейных групп конечной линейной ширины - Дашкова, О.Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
The definition of the linear width of a linear group is introduced. This definition is an analogy
of the BFC-number of a group. The infinite locally finite infinite dimensional linear groups of
finite linear width are investigated. It is proved that these groups contain an Abelian subgroup
of finite index that has finite central (fundamental) dimension.